Way out/way in: How the relationship between WRN and CDK1 may change the fate of collapsed replication forks - Valentina Palermo; Sara Rinalducci; Massimo Sanchez; Francesca Grillini; Annapaola Franchitto; Pietro Pichierri (Molecular & Cellular Oncology, 2017)
Replication-dependent double-strand breaks (DSBs) are the main source of genomic instability as their inaccurate repair stimulates chromosomal rearrangements. In a recent work, we uncover a novel regulatory circuit that involves the Werner's syndrome helicase and CDK1, and that is essential for repair pathway choice at replication-dependent DSBs.